Gender, migration and HIV in rural KwaZulu-Natal, South Africa. - Carol S Camlin (Public Library of Science (PLoS), 2010)
Objectives Research on migration and HIV has largely focused on male migration, often failing to measure HIV risks associated with migration for women. We aimed to establish whether associations between migration and HIV infection differ for women and men, and identify possible mechanisms by which women's migration contributes to their high infection risk. Design Data on socio-demographic characteristics, patterns of migration, sexual behavior and HIV infection status were obtained for a population of 11,677 women aged 15-49 and men aged 15-54, resident members of households within a demographic surveillance area participating in HIV surveillance in 2003-04. Methods Logistic regression was conducted to examine whether sex and migration were independently associated with HIV infection in three additive effects models, using measures of recent migration, household presence and migration frequency. Multiplicative effects models were fitted to explore whether the risk of HIV associated with migration differed for males and females. Further modeling and simulations explored whether composition or behavioral differences accounted for observed associations. Results Relative to non-migrant males, non-migrant females had higher odds of being HIV-positive (adjusted odds ratio [aOR] = 1.72; 95% confidence interval [1.49-1.99]), but odds were higher for female migrants (aOR = 2.55 [2.07-3.13]). Female migrants also had higher odds of infection relative to female non-migrants (aOR = 1.48 [1.23-1.77]). The association between number of sexual partners over the lifetime and HIV infection was modified by both sex and migrant status: For male non-migrants, each additional partner was associated with 3% higher odds of HIV infection (aOR = 1.03 [1.02-1.05]); for male migrants the association between number of partners and HIV infection was non-significant. Each additional partner increased odds of HIV infection by 22% for female non-migrants (aOR = 1.22 [1.12-1.32]) and 46% for female migrants (aOR = 1.46 [1.25-1.69]). Conclusions Higher risk sexual behavior in the context of migration increased women's likelihood of HIV infection.